Interactive Learning with Student Response System to Encourage Students to Provide Peer Feedback - Ponce-Arias, H (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
This study analyzed anonymous peer feedback among two groups of university students—a lower-performing class and a higher-performing class. Students used an audience response system to anonymously comment on each other’s work. Each peer feedback or comment was categorized into one of seven types: Praise+, Praise−, Criticism+, Criticism−, Combined Praise and Criticism, Opinion, and Irrelevant. The plus (+) and minus (−) signs were used to categorize the quality of the feedback. The learning performance of the two groups of students was also analyzed. The main result showed that the lower-performing class (based on the average midterm scores) provided more substantial Criticism+ and Opinion-type comments than the higher-performing students. Contrary to expectation, no significant difference was found between the two classes on the final exam, suggesting that anonymity allowed lower-performing students to express themselves more effectively than higher-performing students, leading them to improve their learning outcomes. © 2023 by the authors.